Identification of Seawater Intrusion Using Geoelectrical Method with Wenner-Schulumberger Configuration: A Case Study in Southern Tolonuo Island, North Halmahera Regency, Indonesia - Nikodemus Kalilu; Bayu Achil Sadjab; Masitah Yusniar; Kurnia Kurnia; Elok Surya Pratiwi (International Journal of Hydrological and Environmental for Sustainability, 2022)
Research on seawater intrusion has been carried out on the southern Tolonuo island, Tobelo sub-district, North Halmahera Regency, Indonesia using the Wenner-Schlumberger configuration resistivity geoelectric method supported by the Naniura NRD 300 HF tool, this study aims to determine the distribution pattern of seawater intrusion and to determine the resistivity value of each subsurface rock layer in the study area. The measurement results are processed using the RES2DINV software to obtain a 2-D pseudo resistivity section that describes the distribution value of the layer that the soil surface is shown in color images. The measurement results on line 1 show that there is seawater intrusion with a resistivity value range of 0.338 m - 2.44 m which is at 4 â€“ 20 meters with a certain pattern, line 2 also has sea water intrusion at a depth of 5 m â€“ 20 m with a resistivity value of 1.31 Î©m â€“ 6.50 Î©m. On line 3, it is clear that there is a good correlation between the intersection of line 1 and line 2, where there is a low resistivity contrast on the line 1 with a stretch of 35 m â€“ 50 m at a depth of 10 m â€“ 20 m and the line 2 with a span of 80 m - 100 m at a depth of 10 m - 20 m. The distribution pattern of seawater intrusion from the south to the north of Tolonou Village with a wide range of up to 200 meters from residential areas from the shoreline. The research area has layers of clay rock with a resistivity value between 30 â€“ 80 Î©m, and breccia rocks around it with a resistivity value of 100 â€“ 200 Î©m. On the other hand, between clay and breccia there is impermeable rock which is thought to be conglomerate rock with a resistivity value of 200-500 Î©m, besides that in the study area there is also a layer suspected to be a groundwater aquifer layer with a resistivity value (Ï) < 10 m.